Fruit quality, anthocyanin and total phenolic contents, and antioxidant activities of 45 blueberry cultivars grown in Suwon, Korea - Kim, Jin Gook; Kim, Hong Lim; Kim, Su Jin; Park, Kyo-Sun (Journal of Zhejiang University. B. Science, 2013)
Blueberry fruits from 45 commercial cultivars （39 northern highbush and 6 half highbush blueberry） grown in Suwon,Korea were analyzed for fruit size,soluble solids content,titratable acidity,total anthocyanin content,total phenolic content,and antioxidant activity.Fruit characteristics varied widely among the 45 blueberry cultivars.Fruit weight ranged from 0.9 to 3.6 g,soluble solids content from 8.3 to 14.3 °Brix,and titratable acidity from 0.8% to 3.6%.Antioxidant activity ranged from 0.7 to 2.1 mg of quercetin equivalents per gram of fresh berries in different blueberry cultivars.Among the 45 blueberry cultivars,high amounts of anthocyanins and polyphenols,and high antioxidant activity were observed in ‘Elliott＇,‘Rubel＇,‘Rancocas＇,and ‘Friendship＇.